Pengaruh Kepuasan dan Citra Destinasi terhadap E-WOM dalam Konteks Wisata Sejarah: Studi Kasus Pengunjung Destinasi Wisata Sejarah Makam Teuku Umar - Ade Angga Saputra (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of visitor satisfaction and destination image on Electronic Word of Mouth (E-WOM) at the Teuku Umar Historical Tourism Site. This research employed a quantitative approach with an associative research design. The sampling technique used was non-probability sampling, with a total sample of 100 respondents determined using the Lemeshow formula. Data were collected through questionnaires distributed to visitors of the Teuku Umar Historical Tourism Site and analyzed using SmartPLS 4.0. The results showed that visitor satisfaction had a positive and significant effect on Electronic Word of Mouth (E-WOM), with a T-statistic value of 2.898 and a P-value of 0.004. Destination image also had a positive and significant effect on Electronic Word of Mouth (E-WOM), with a T-statistic value of 15.222 and a P-value of 0.000. Furthermore, visitor satisfaction and destination image simultaneously explained 78.9% of the variance in Electronic Word of Mouth (E-WOM), while the remaining 21.1% was influenced by other factors outside the scope of this study. The findings indicate that destination image is the most dominant variable influencing Electronic Word of Mouth (E-WOM).